Murder can haunt your handiwork - Pressey, Rose (Pressey, Rose. Haunted craft fair mystery., 2020)
"Rising up against the beautiful backdrop of the Blue Ridge Mountains, the Biltmore Estate is a magnificent mansion in Asheville, North Carolina, built as a summer home for George Washington Vanderbilt II--yes, of those Vanderbilts--during the Gilded Age. Nowadays, it's the site of an annual craft fair. Unfortunately, it's also about to become a crime scene... Celeste is hard to miss as she pulls up with her pink and white Shasta trailer and adorable Chihuahua, Van Gogh--Van for short. But before she can show off her artwork at the fair, a tour guide is found strangled by a velvet rope barrier and a valuable painting goes missing. With a rogues' gallery of sketchy suspects, Celeste welcomes the help of a pair of handsome detectives--and a ghost with a special interest in the case..."--Page 4 of cover.